Neutron transition strengths of 21+ states in the neutron-rich oxygen isotopes determined from inelastic proton scattering - Nguyễn, Đăng Chiến (APS publications, 2024)
A coupled-channel analysis of the 18,20,22O(p,p′) data has been performed to determine the neutron transition strengths of the 2+1 states in oxygen targets, using the microscopic optical potential and inelastic form factor calculated in the folding model. A complex density- and isospin-dependent version of the CDM3Y6 interaction was constructed, based on the Brueckner-Hartree-Fock calculation of nuclear matter, for the folding model input. Given an accurate isovector density dependence of the CDM3Y6 interaction, the isoscalar (δ0) and isovector (δ1) deformation lengths of the 2+1 states in 18,20,22O have been extracted from the folding model analysis of the (p,p′) data. A specific N dependence of δ0 and δ1 has been established which can be linked to the neutron shell closure occurring at N approaching 16. The strongest isovector deformation was found for the 2+1 state in 20O, with δ1 about 2.5 times larger than δ0, which indicates a strong core polarization by the valence neutrons in 20O. The ratios of the neutron/proton transition matrix elements (Mn/Mp) determined for the 2+1 states in 18,20O have been compared with those deduced from the mirror symmetry, using the measured B(E2) values of the 2+1 states in the proton-rich 18Ne and 20Mg nuclei, to discuss the isospin impurity in the 2+1 excitation of the A=18, T=1 and A=20, T=2 isobars.